2010
DOI: 10.1111/j.1445-2197.2010.05310.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of an acute assessment and review area for general surgical patients

Abstract: The introduction of a dedicated SARA significantly reduced hospital stay and improved efficiencies of the emergency department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Total monthly bed days for all biliary disease patients have decreased over time, indicating overall benefits not only to patients, but also to the hospital. The introduction of a dedicated surgical assessment and review area (SARA) at Christchurch Public Hospital in March 2008 has been previously shown to have reduced hospital stay and improved inefficiencies in all acute surgical admissions 20 . This is not reflected in the preoperative bed day analysis for patients undergoing index cholecystectomy, in which time to acute theatre admission appears unchanged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Total monthly bed days for all biliary disease patients have decreased over time, indicating overall benefits not only to patients, but also to the hospital. The introduction of a dedicated surgical assessment and review area (SARA) at Christchurch Public Hospital in March 2008 has been previously shown to have reduced hospital stay and improved inefficiencies in all acute surgical admissions 20 . This is not reflected in the preoperative bed day analysis for patients undergoing index cholecystectomy, in which time to acute theatre admission appears unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of a dedicated surgical assessment and review area (SARA) at Christchurch Public Hospital in March 2008 has been previously shown to have reduced hospital stay and improved inefficiencies in all acute surgical admissions. 20 This is not reflected in the preoperative bed day analysis for patients undergoing index cholecystectomy, in which time to acute theatre admission appears unchanged. The reduction in readmission rates brought about by a change in the practice of index cholecystectomy 10,17 is probably also reflected in the decrease in total monthly bed use.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital LOS was assessed in 19 studies. 10,[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][29][30][31] This measure was generally not clearly defined in these studies. Of the 8 studies that provided definitions, 4 looked at the time interval from inpatient admission to discharge, 3 considered the time from triage to discharge, and 1 mea sured emergency department arrival to discharge.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The published literature from Australasia has described numerous strategies for improving acute surgical care including alterations to surgical rosters, reorganization of available work space and dedicated acute surgical units 10–13 . The dedicated acute surgical unit has been shown to improve efficiency and enhance patient outcomes 10,14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…9 The published literature from Australasia has described numerous strategies for improving acute surgical care including alterations to surgical rosters, reorganization of available work space and dedicated acute surgical units. [10][11][12][13] The dedicated acute surgical unit has been shown to improve efficiency and enhance patient outcomes. 10,14,15 Previous authors have also commented upon the positive changes in work culture at their respective institutions and increased satisfaction among those involved in the system.…”
Section: Introductionmentioning
confidence: 99%